2017
DOI: 10.1007/s00253-017-8542-8
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds from endophytic fungi as innovative postharvest control of Fusarium oxysporum in cherry tomato fruits

Abstract: To assess their potential as biopesticides, the effect on the growth of phytopathogen Fusarium oxysporum of six volatile organic compounds from endophytic fungi was studied in vivo and in vitro; compounds were used both as a mixture and individually. In vivo studies were performed inoculating the pathogen into cherry tomatoes, while the in vitro antifungal effect was studied using agar dilution and gas phase methods. Also, the morphology of the hyphae exposed to these compounds was analyzed. Moreover, the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 44 publications
0
41
0
3
Order By: Relevance
“…The results indicated that these compounds exhibited concentration-dependent anti-fungal activity individually but have better action and control synergistically. Thus, the mixture of six VOCs may be used for the control of Fusarium oxysporum in tomatoes [ 96 ].…”
Section: Antifungal Potential Of Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…The results indicated that these compounds exhibited concentration-dependent anti-fungal activity individually but have better action and control synergistically. Thus, the mixture of six VOCs may be used for the control of Fusarium oxysporum in tomatoes [ 96 ].…”
Section: Antifungal Potential Of Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…Ocimene and the mixture induced a vacuolization process and thickening and thinning on the middle and the tips, respectively. Finally, an inhibitory effect on the respiration were observed with all treatments, which could be attributed to the proliferation of vacuoles and the severe vacuolization process provoked by the rupture of hyphae [88]. VOCsʼ mixture showed the greatest oxygen consumption inhibition (97.1 %) after 8 h incubation (IC 50 = 183.9 µg/mL).…”
Section: Hypoxylon Anthochroummentioning
confidence: 92%
“…In this context, E. gomezpompae was isolated from surface sterilized leaves of the medicinal plant C. acuminata [73]. A chemical investigation of the mycelium of E. gomezpompae resulted in the isolation of eight naphthoquinone-spiroketals, namely, preussomerins EG 1 -EG 4 (85)(86)(87)(88), palmarumycins EG 1 (89), CP 2 (90), CP 17 (91), and CP 19 (92) as well as 50 [74,75] (▶ Fig. 14).…”
Section: Endophytes From Plants Collected In El Eden Ecological Resermentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, a pró-região atua estabilizando o estado de transição que separa a forma nativa da enzima em sua conformação terciária ativa (SOHL et al, 1998 (MEDINA-ROMERO et al, 2017;LESLIE;SUMMERELL, 2006).…”
Section: Subtilisinasunclassified